Communism's shadow historical legacies and contemporary political attitudes - Pop-Eleches, Grigore; Tucker, Joshua A. (Joshua Aaron) 1971- (Princeton, New Jersey Princeton University Press, 2017)
It has long been assumed that the historical legacy of Soviet Communism would have an important effect on post-communist states. However, prior research has focused primarily on the institutional legacy of communism. "Communism's Shadow" instead turns the focus to the individuals who inhabit post-communist countries, presenting a rigorous assessment of the legacy of communism on political attitudes. Post-communist citizens hold political, economic, and social opinions that consistently differ from individuals in other countries. Grigore Pop-Eleches and Joshua Tucker introduce two distinct frameworks to explain these differences, the first of which focuses on the effects of living in a post-communist country, and the second on living through communism. Drawing on large-scale research encompassing post-communist states and other countries around the globe, the authors demonstrate that living through communism has a clear, consistent influence on why citizens in post-communist countries are, on average, less supportive of democracy and markets and more supportive of state-provided social welfare. The longer citizens have lived through communism, especially as adults, the greater their support for beliefs associated with communist ideology--the one exception being opinions regarding gender equality.
Communism's shadow -- Living through communism -- Methods and data -- Democracy -- Markets -- Social welfare -- Gender equality -- Temporal resilience and change -- Legacies and communism.
Includes bibliographical references (pages 313-331) and index.
Keywords: Post-communism -- Europe, Eastern